Sepsis due to Aeromonas hydrophila: Case report - Kanne, Padmaja; Lakshmi, Vemu; Dakshinamurthy, Kaligotla (International Journal of Infection Control, 2013)
Although there are ever increasing reports of extraintestinal human infections caused by Aeromonads, in both immunocompromised and immunocompetent patients,sepsis remaims uncommon.We report a rare case of Aeromonas hydrophila sepsis in an immunocompromised individual.The case highlights the clinical significance of A. hydrophila as blood stream infection.